LA MUJER DEL CÉSAR EN LA POLÍTICA ESPAÑOLA EN SU ETAPA DEMOCRÁTICA - Luis J. Tosina Fernández (Proverbium, 2019)
The use of proverbs by politicians is a rather frequent phenomenon, which has motivated some paremiological studies, such as those by Mieder (2005, 2009, 2010) or Mieder and Bryan (1995, 1997), centered in analyzing the use that certain political figures have made of proverbs. The present study takes a proverb that seems particularly adequate for its use by political representatives, given its origin and purpose, to try to determine whether these characteristics make the proverb Caesar’s wife must be above suspicion particularly adequate for use in the parliamentary sphere. For this purpose, the transcripts of parliamentary speeches since the restoration of the democratic system have been examined in search of uses of the prov-erb, analyzing aspects that seemed essential, such as who used the proverb and with what purpose.